EQUIPMENT GRAFTING IN TELECOMMUNICATION INDUSTRY(CASE STUDY NIGERIA PSTN) (Nigerian Journal of Technology, 2009)
The growth and pace of any industry is a veritable estimation of its viability. The telecommunications industry all over the world is ever burgeoning. Its growth is buoyed by development and technologies. These innovations do not necessarily have to instantaneously supplant the old rather they are procedurally applied to the existing network in the form of Upgrades and Expansion efforts. This paper appraises these grafting processes. It introduces the subject matter, highlights the performance capabilities and usage constraints of a variety of switching and transmission equipment. It also gives insight into the on-going grafting efforts in NITEL.